Cyclodextrin-assisted fluorescein decoration of gold nanoclusters for ratiometric and selective Hg2+ analysis - Sun, Siyuan; Yuan, Zhiqin (Frontiers in Analytical Science, 2025)
IntroductionThe construction of nanomaterial-based ratiometric detection systems usually requires covalent modification, which undergoes reactive environments and may change the natural properties of supporting nanomaterials.MethodsIn this study, dualemissive and fluorescein-decorated gold nanoclusters (F-Au NCs) through cyclodextrin-supported host–guest interaction (non-covalent modification) are explored as ratiometric Hg2+ nanoprobes through d10–d10-interactioncaused fluorescence quenching of Au NCs.Results and DiscussionThe fluorescein decoration only provides a fluorescent internal reference but does not change the Hg2+-Au NCs affinity nature. Ratiometric and selective Hg2+ detection is achieved through the proposed F-Au NC probes with a limit of detection of 15 nM. The Hg2+ analysis in river water samples with small relative standard deviations validates the practical application of these probes.